GE_GERICHTE P/4336/2017 vom 29. September 2017 - GE Cour de justice (2017)
ORDONNANCE PÉNALE ; OPPOSITION TARDIVE ; RESTITUTION DU DÉLAI ; DÉLAI ; EMPÊCHEMENT NON FAUTIF ; FRACTURE | CPP.354; CPP.94; CPP.91.al2